Engaging with parents in early years settings - Jackson, Dianne; Needham, Martin; Sage eBooks ([Los Angeles] : SAGE, 2016)
Whether working in children's centres, outreach and dual-focused services, preschools, kindergartens or schools, this book helps readers develop the skills and strategies to work alongside parents whatever their role.
Includes index.
Specialized.
Description based on online resource; title from home page (viewed on January 20, 2016).
Keywords: Education, Elementary -- Parent participation -- Great Britain; Parent-teacher relationships -- Great Britain; Electronic books